Efforts to Increase Activities and Learning Outcomes Through Macromedia Fash 8 Collaboration and Flash Cards for Class II Semester I Students at SDN Pulorejo 02 Academic Year 2022/2023 - Sumiyati, Sumiyati (Al Hikmah: Journal of Education, 2022)
The aims of this study are: 1) To describe the PAI learning process through the collaboration of Macromedia Fash 8 and Flash Card, 2) To find out whether the application of the collaboration of Macromedia Fash 8 and Flash Card can improve student learning activities, 3) To find out whether the application of MacromediaFash 8 and Flash Cards can improve learning outcomes for Class II SDN Pulorejo 02. This classroom action research uses a qualitative descriptive method. The subject of the research is the second semester of the first semester of the 2022/2023 academic year at SD Negeri Pulorejo 02, Winong District, Pati Regency. The results of the observation of the learning process show that the collaboration of Macromedia Fash 8 interactive media and Flash Card has increased the average score from 2.69 in the good category in the first cycle to 3.63 with the very good category in the second cycle. Data from observations on student learning activities also showed an average increase from 2.96 in the first cycle to 3.54 in the second cycle. Learning outcomes also showed an increase, in the initial conditions students completed the KKM as many as 5 students or 42%, while those who had not completed were 7 students or 58% with an average score of 63.33. It increased in the first cycle, namely students who completed the KKM by 8 students or 67%, while students who had not completed the KKM were 4 students or 33% with an average score of 78.25. Increasingly in the second cycle, there are 11 students who have completed the KKM or 92%, while the students who have not completed the KKM are only 1 student or 8% with an average score of 91.00. This shows that student learning outcomes have increased significantly.